Láminas delgadas magneto-ópticas. (B-IMEYMAT, 2018)
Domínguez-de-la-Vega. M, Aguinaco-Martín. A, Bakkali. H, Blanco-Ollero. E, García-Domínguez. RP, González-Leal. JM, Litrán-Ramos. R, Mánuel-Delgado. JM, Márquez-Navarro. EJ, Ramírez-del-Solar. M.